Радіочастотна нейроабляція як метод лікування больового синдрому в консервативному лікуванні гонартрозу - Головаха, Максим Леонідович; Білих, Євген Олегович; Golovakha, M. L.; Bilykh, Ye. O. (My University, 2019)
Боль при гонартрозе — одна из частых причин обращения пациентов к врачу — считается ноцицептивной, поэтому при лечении рационально целенаправленно воздействовать на структуры, которые ее продуцируют. Радиочастотная нейроабляция (РЧНА) позволяет влиять на ноцицептивный механизм в структурах, проводящих болевые импульсы. Цель: определить эффективность применения РЧНА при лечении болевого синдрома при гонартрозе. Методы: выполнено открытое рандомизированное исследование, в которое включено 44 пациента с гонартрозом III стадии с преобладанием болевого синдрома одного коленного сустава. Больных разделили на две группы: исследования (n = 22) и сравнения (n = 22). Для лечения болевого синдрома в обеих группах назначали базисную терапию артроза, а в группе исследования дополнительно — РЧНА геникулярных нервов. Оценивали интенсивность болевого синдрома по ВАШ, функциональный статус и качество жизни больных — с использованием опросника WOMAC через 2 недели, 1 и 3 мес. от начала лечения. Pain syndrome is one of the most frequent reasons for visiting a doctor of elderly patients with knee osteoarthritis. Pain caused by knee osteoarthritis is nociceptive; therefore, in the treatment of the knee osteoarthritis, it is rational to provide a targeted impact on the structures that produce the pain. Radiofrequency neuroablation (RFNA) allows induce the nociceptive mechanism in the structures conducting pain impulses. Objective: to evaluate the effectiveness of radiofrequency neuroablation in the treatment of pain syndrome in patients with knee osteoarthritis. Methods: the open controlled randomized study included treatment results analysis of 44 patients with knee osteoarthritis of the third stage with predominance of pain in one of the knee joints. Patients were divided into two groups: the s tudy g roup (n = 22) a nd t he c omparison g roup (n = 22). Patients of both groups for the treatment of knee joint pain received osteoarthritis basis therapy. Patients in the study group additionally had RFNA of the genicular nerves. The intensity of the pain syndrome was measured with visual analog scale (VAS) and the functional status and quality of life of patients was analyzed using the WOMAC questionnaire in terms of 2 weeks, 1 and 3 months after the beginning of the treatment.
Radiofrequency neuroablation as a treatment method for pain syndrome in conservative treatment of knee osteoarthritis
Keywords: больовий синдром; гонартроз; радіочастотна нейроабляція